Elemental analysis of wines from South America and their classification according to country - Bentlin,Fabrina R. S (2011)
Major, minor and trace elements in wines from wine-producing countries in South America (Argentina, Brazil, Chile, and Uruguay) were determined. Inductively coupled plasma optical emission spectrometry (ICP OES) and inductively coupled plasma mass spectrometry (ICP-MS) combined with pneumatic and/or ultrasonic nebulization were used. The concentrations of 45 elements (Al, Ag, As, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Gd, Ho, K, La, Li, Lu, Mg, Mn, Mo, Na, Nd, Ni, P, Pb, Pr, Rb, Sb, Sn, Se, Sm, Sr, Tb, Ti, Tl, Tm, U, V, Yb, and Zn) in 53 red wines were determined. By means of multivariate analysis, the wines could be discriminated according to the country of origin, regardless of the type of grape. The discriminant elements were Tl, U, Li, Rb, and Mg.